2017
DOI: 10.18869/acadpub.ibj.21.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Expression of Connexin36 and Connexin43 during Epileptogenesis in Pilocarpine Model of Epilepsy

Abstract: Background:Gap junctions (GJs) provide direct intercellular communications that are formed by hexameric protein subunits, called connexin (Cx). The role of Cxs in epileptogenesis has not received sufficient attention. Hippocampus with a critical function in epileptogenesis has a wide network of GJs. We examined the protein expression levels of hippocampal Cx36 (the prominent Cx present between GABAergic interneurons) and Cx43 (the main Cx expressed by astrocytes) during epileptogenesis in the pilocarpine model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
3
11
1
Order By: Relevance
“…To further understand the relationship between Cx36 and hyperactivity, we asked the reciprocal question: how does hyperactivity affect Cx36? Similar to the seizure susceptibility studies, work to identify this relationship has remained conflicting (Söhl et al, 2000 ; Laura et al, 2015 ; Motaghi et al, 2017 ; Wu et al, 2017 ). Previous approaches used to address this question (e.g., qPCR, western blot) lacked the necessary spatial resolution to determine if the effects of hyperactivity on Cx36 vary based on the brain region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further understand the relationship between Cx36 and hyperactivity, we asked the reciprocal question: how does hyperactivity affect Cx36? Similar to the seizure susceptibility studies, work to identify this relationship has remained conflicting (Söhl et al, 2000 ; Laura et al, 2015 ; Motaghi et al, 2017 ; Wu et al, 2017 ). Previous approaches used to address this question (e.g., qPCR, western blot) lacked the necessary spatial resolution to determine if the effects of hyperactivity on Cx36 vary based on the brain region.…”
Section: Discussionmentioning
confidence: 99%
“…In rodent seizure models and epilepsy patient post-mortem samples, some groups have found that Cx36 expression was increased (Collignon et al, 2006 ; Laura et al, 2015 ; Wu et al, 2017 ), while others found decreased Cx36 expression (Söhl et al, 2000 ; Condorelli et al, 2003 ) or no change (Motaghi et al, 2017 ). Furthermore, even though seizures result in brain-wide changes in neuronal connectivity (Morgan et al, 2010 ), seizure-induced changes in Cx36 expression had only been examined in the dorsal telencephalon (cortex and hippocampus) (Condorelli et al, 2003 ; Laura et al, 2015 ; Motaghi et al, 2017 ; Wu et al, 2018 ). Potential changes to Cx36 expression in other brain areas following neuronal hyperactivity remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To further understand the relationship between Cx36 and hyperactivity, we asked the reciprocal question: how does hyperactivity affect Cx36? Similar to the seizure susceptibility studies, work to identify this relationship has remained conflicting (Laura et al, 2015;Motaghi et al, 2017;Söhl et al, 2000;X. Wu et al, 2017).…”
Section: Ptz Induced Hyperactivity Causes a Regionally-specific Decrementioning
confidence: 99%
“…In rodent seizure models and epilepsy patient post-mortem samples, some groups have found that Cx36 expression was increased (Collignon et al, 2006;Laura, Xóchitl, Anne, & Alberto, 2015;X. Wu, Wang, Hao, & Feng, 2017), while others found decreased Cx36 expression (Condorelli, Trovato-Salinaro, Mudo, Mirone, & Belluardo, 2003;Söhl et al, 2000) or no change (Motaghi, Sayyah, Babapour, & Mahdian, 2017). Furthermore, even though seizures result in brain-wide changes in neuronal connectivity (Morgan, Gore, & Abou-Khalil, 2010), seizure-induced changes in Cx36 expression had only been examined in the dorsal telencephalon (cortex and hippocampus) (Condorelli et al, 2003;Laura et al, 2015;Motaghi et al, 2017;X.…”
Section: Introductionmentioning
confidence: 99%
“…In rodent seizure models and epilepsy patient post-mortem samples, some groups have found that Cx36 expression was increased (Collignon et al, 2006;Laura et al, 2015;Wu et al, 2017), while others found decreased Cx36 expression (Söhl et al, 2000;Condorelli et al, 2003) or no change (Motaghi et al, 2017). Furthermore, even though seizures result in brain-wide changes in neuronal connectivity (Morgan et al, 2010), seizure-induced changes in Cx36 expression had only been examined in the dorsal telencephalon (cortex and hippocampus) (Condorelli et al, 2003;Laura et al, 2015;Motaghi et al, 2017;Wu et al, 2018). Potential changes to Cx36 expression in other brain areas following neuronal hyperactivity remain unknown.…”
Section: Introductionmentioning
confidence: 99%